C9orf72-Associated Dipeptide Repeat Expansions Perturb ER-Golgi Vesicular Trafficking, Inducing Golgi Fragmentation and ER Stress, in ALS/FTD - Jessica Sultana; Audrey M. G. Ragagnin; Sonam Parakh; Sayanthooran Saravanabavan; Kai Ying Soo; Marta Vidal; Cyril Jones Jagaraj; Kunjie Ding; Sharlynn Wu; Sina Shadfar; Emily K. Don; Anand Deva; et al. (Molecular Neurobiology, 2024)
Hexanucleotide repeat expansions (HREs) in the chromosome 9 open reading frame 72 ( C9orf72 ) gene are the most frequent genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Both are debilitating neurodegenerative conditions affecting either motor neurons (ALS) in the brain and spinal cord or neurons in the frontal and/or temporal cortical lobes (FTD). HREs undergo repeat-associated non-ATG (RAN) translation on both sense and anti-sense strands, generating five distinct dipeptide repeat proteins (DPRs), poly-GA, -GR, -GP, -PA and -PR. Perturbed proteostasis is well-recognised in ALS pathogenesis, including processes affecting the endoplasmic reticulum (ER) and Golgi compartments. However, these mechanisms have not been well characterised for C9orf72-mediated ALS/FTD. In this study we demonstrate that C9orf72 DPRs polyGA, polyGR and polyGP (× 40 repeats) disrupt secretory protein transport from the ER to the Golgi apparatus in neuronal cells. Consistent with this finding, these DPRs also induce fragmentation of the Golgi apparatus, activate ER stress, and inhibit the formation of the omegasome, the precursor of the autophagosome that originates from ER membranes. We also demonstrate Golgi fragmentation in cells undergoing RAN translation that express polyGP. Furthermore, dysregulated ER-Golgi transport was confirmed in C9orf72 patient dermal fibroblasts. Evidence of aberrant ER-derived vesicles in spinal cord motor neurons from C9orf72 ALS patients compared to controls was also obtained. These data thus confirm that ER proteostasis and ER-Golgi transport is perturbed in C9orf72-ALS in the absence of protein over-expression. Hence this study identifies novel molecular mechanisms associated with the ER and Golgi compartments induced by the C9orf72 HRE.

Speciation across biomes: Rapid diversification with reproductive isolation in the Australian delicate mice - Emily Roycroft; Fred Ford; Till Ramm; Rhiannon Schembri; William G. Breed; Phoebe A. Burns; Kevin C. Rowe; Craig Moritz (Molecular Ecology, 2024)
Phylogeographic studies of continental clades, especially when combined with palaeoclimate modelling, provide powerful insight into how environment drives speciation across climatic contexts. Australia, a continent characterized by disparate modern biomes and dynamic climate change, provides diverse opportunity to reconstruct the impact of past and present environments on diversification. Here, we use genomic‐scale data (1310 exons and whole mitogenomes from 111 samples) to investigate Pleistocene diversification, cryptic diversity, and secondary contact in the Australian delicate mice (Hydromyini: Pseudomys ), a recent radiation spanning almost all Australian environments. Across northern Australia, we find no evidence for introgression between cryptic lineages within Pseudomys delicatulus sensu lato, with palaeoclimate models supporting contraction and expansion of suitable habitat since the last glacial maximum. Despite multiple contact zones, we also find little evidence of introgression at a continental scale, with the exception of a potential hybrid zone in the mesic biome. In the arid zone, combined insights from genetic data and palaeomodels support a recent expansion in the arid specialist P. hermannsburgensis and contraction in the semi‐arid P. bolami . In the face of repeated secondary contact, differences in sperm morphology and chromosomal rearrangements are potential mechanisms that maintain species boundaries in these recently diverged species. Additionally, we describe the western delicate mouse as a new species and recommend taxonomic reinstatement of the eastern delicate mouse. Overall, we show that speciation in an evolutionarily young and widespread clade has been driven by environmental change, and potentially maintained by divergence in reproductive morphology and chromosome rearrangements.

Population genomics of decline and local extinction in the endangered Australian Pookila - Phoebe A. Burns; Kevin C. Rowe; Marissa L. Parrott; Emily Roycroft (Biological Conservation, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Calcium‐dependent site‐switching regulates expression of the atypical iam pilus locus in Vibrio vulnificus - Meng Pu; Emily Storms; Dan M. Chodur; Dean A. Rowe‐Magnus (Environmental Microbiology, 2020)
Summary The opportunistic human pathogen Vibrio vulnificus inhabits warm coastal waters and asymptomatically colonizes seafood, most commonly oysters. We previously characterized an isolate that exhibited greater biofilm formation, aggregation and oyster colonization than its parent. This was due, in part, to the production of a Type IV Tad pilus (Iam). However, the locus lacked key processing and regulatory genes required for pilus production. Here, we identify a pilin peptidase iamP , and LysR‐type regulator (LRTR) iamR , that fulfil these roles and show that environmental calcium, which oysters enrich for shell repair and growth, regulates iam expression. The architecture of the iam locus differs from the classical LRTR paradigm and requires an additional promoter to be integrated into the regulatory network. IamR specifically recognized the iamR promoter ( P iamR ) and the intergenic iamP ‐ iamA region ( P iamP‐A ). P iamR exhibited classical negative auto‐regulation but, strikingly, IamR inversely regulated the divergent iamP and iamA promoters in a calcium‐dependent manner. Moreover, expression of the c‐di‐GMP and calcium‐regulated, biofilm‐promoting brp exopolysaccharide was IamA‐dependent. These results support a scenario in which the calcium‐enriched oyster environment triggers IamP‐mediated processing of prepilin amassed in the periplasm for rapid pilin elaboration and subsequent BRP production to promote colonization.

Measuring sperm swimming performance in birds: effects of dilution, suspension medium, mechanical agitation, and sperm number - Emily R. A. Cramer; Melissah Rowe; Fabrice Eroukhmanoff; Jan T. Lifjeld; Glenn-Peter Sætre; Arild Johnsen (Journal of Ornithology, 2019)

Rockfall risk management using a pre-failure deformation database - Ryan A. Kromer; Emily Rowe; Jean Hutchinson; Matt Lato; Antonio Abellán (Landslides, 2018)

Erratum to: an analysis of failure mechanism constraints on pre-failure rock block deformation using TLS and roto-translation methods - Emily Rowe; D. Jean Hutchinson; Ryan A. Kromer (Landslides, 2018)

An analysis of failure mechanism constraints on pre-failure rock block deformation using TLS and roto-translation methods - Emily Rowe; D. Jean Hutchinson; Ryan A. Kromer (Landslides, 2018)

3D Cosmic Ray Muon Tomography from an Underground Tunnel - Elena Guardincerri; Charlotte Rowe; Emily Schultz-Fellenz; Mousumi Roy; Nicolas George; Christopher Morris; Jeffrey Bacon; Matthew Durham; Deborah Morley; Kenie Plaud-Ramos; Daniel Poulson; Diane Baker; et al. (Pure and Applied Geophysics, 2017)

Testing a post-copulatory pre-zygotic reproductive barrier in a passerine species pair - Emily R. A. Cramer; Terje Laskemoen; Fabrice Eroukhmanoff; Fredrik Haas; Jo S. Hermansen; Jan T. Lifjeld; Melissah Rowe; Glenn-Peter Sætre; Arild Johnsen (Behavioral Ecology and Sociobiology, 2014)